Differentiation between Enamines and Tautomerizable Imines Oxidation Reaction Mechanism using Electron-Vibration-Vibration Two Dimensional Infrared Spectroscopy - Fengqin Long; Zheng Chen; Keli Han; Lu Zhang; Wei Zhuang (Molecules, 2019)
Intermediates lie at the center of chemical reaction mechanisms. However, detecting intermediates in an organic reaction and understanding its role in reaction mechanisms remains a big challenge. In this paper, we used the theoretical calculations to explore the potential of the electron-vibration-vibration two-dimensional infrared (EVV-2DIR) spectroscopy in detecting the intermediates in the oxidation reactions of enamines and tautomerizable imines with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO). We show that while it is difficult to identify the intermediates from their infrared and Raman signals, the simulated EVV-2DIR spectra of these intermediates have well resolved spectral features, which are absent in the signals of reactants and products. These characteristic spectral signatures can, therefore, be used to reveal the reaction mechanism as well as monitor the reaction progress. Our work suggests the potential strength of EVV-2DIR technique in studying the molecular mechanism of organic reactions in general.